Comments on statutory regulation of administrative penalties (Ius Novum, 2020)
Due to the repressive nature and painfulness of pecuniary administrative penalties, the legislator decided to regulate general rules of their imposition. The framework regulations in the field were introduced to the Act of 14 June 1960: Code of Administrative Procedure. These are applicable only when separate provisions do not contain special solutions. This causes a critical practical problem concerning the relationship between the general provisions of Part IVa CAP and the provisions of special statutes. The article aims to present the origin of the general provisions concerning pecuniary administrative penalties, to draw attention to the most important aspects of the application of new regulations with the use of examples illustrating a penalty for the occupation of a road lane, and to propose a solution to the conflict in the relationship between the application of the Act on public finance, the Tax Law and the Code of Administrative Procedure in relation to administrative penalties. The phrasing of the provisions is unclear and poses a risk of considerable adjudicating discrepancies, which will create a necessity to pass an abstract resolution concerning this issue by the Supreme Administrative Court. The author uses an analytic-dogmatic and empiric-legal research method in the article.
Keywords: application of penalties; res iudicata; amendment to the Code of Administrative Procedure; sanction; obligation